Excited-state hydrogen detachment from a tris-(o-phenylenediamine) iron(ii) complex in THF at room temperature. Issue 98 (7th December 2020) - Nakada, Akinobu; Koike, Takuji; Matsumoto, Takeshi; Chang, Ho-Chol
Abstract : Excited-state hydrogen detachment of tris-( o -phenylenediamine) iron(ii ) complex was elucidated in THF under an N2 atmosphere at room temperature. Abstract : We previously reported that a tris-( o -phenylenediamine) iron(ii ) complex promotes photochemical H2 generation and C–H carboxylation of o -phenylenediamine without any additives under N2 and CO2 atmospheres, respectively, in tetrahydrofuran at room temperature. Herein, the key mechanistic process, namely, excited-state hydrogen detachment from the o -phenylendiamine moiety, is demonstrated under an N2 atmosphere.